Praksisveilederes opplevelse av et nytt veilednings- og vurderingsverktøy for sykepleierstudenter i praksis – en evalueringsstudie - Julnes, Signe Gunn; Grønvik, Cecilie Katrine Utheim; Eines, Trude Fløystad (Nordisk tidsskrift for helseforskning, 2015)
Experience of mentors using a new guidance and assessment model for nursing students. This paper explores the experience of mentors when using a new guidance and assessment model for nursing students during practical studies. The National Qualifications Framework for higher education is implemented in the new model. During 2012, 22 mentors participated in five different focus groups. The data were analyzed using deductive and inductive stepwise analysis. The participants found the new model quite challenging at first. With experience, the mentors became more confident in providing guidance and more constructive and objective assessment. This study underscores the importance of common pedagogical understanding of the model among mentors. We find that active use of the new model improves both guidance and assessment of nursing students in practical studies.